The Influence of Income and Consumptive Lifestyle on Interest in Using Shopee Paylater in Gen Z - Jalaludin, Jalaludin; Bahri, Saepul; Kusumaningtias, Ajeng (Maro: Jurnal Ekonomi Syariah dan Bisnis, 2025)
This study aims to analyze the partial and simultaneous effects of income and consumptive lifestyle on the interest in using Shopee PayLater among STIES Indonesia Purwakarta students of the 2021 cohort. The method used is descriptive quantitative with purposive sampling technique on 33 respondents from a total population of 107 students. The analysis results show that income has a positive and significant effect on the interest in using Shopee PayLater (tcount = 3.667; sig = 0.001; R² = 0.578), as does a consumptive lifestyle (tcount = 9.736; sig = 0.000; R² = 0.754). Simultaneously, both variables had an 80.4% influence on interest in using the service (Fhitung = 61.479; sig = 0.000; R² = 0.804). These findings confirm that financial aspects and consumptive behavior are the main indicators of student preferences for paylater services. Practical implications include the need for behavior-based marketing strategies and the strengthening of digital financial literacy in higher education environments.